(untitled) (Ustozlar uchun, 2026)
Characteristic features of hemoglobinuric nephrosis in accidental and suicidal poisoning with acetic acid. But the degree of damage to the kidney parenchyma is most clearly manifested if there is acute or chronic stress before poisoning.